Impact of Differentiated Customer Service, Brand Trust, Brand Commitment, and Brand Salience on Brand Advocacy - Hassan, Muhammad; Rafi, Arslan; Kazmi, Syed Sibtain (International Review of Management and Marketing, 2016)
The purpose of this study is to extensively identify the impact of variables that tend to make the customers into advocates. Today companies have to focus on customers more frequently and consistently than they focus on advertisements and promotions because of competitive market. This study will help the brands to focus on what actually a consumer wants and why making advocates is necessary. In order to justify the developed hypotheses, young males and females from the population of the universities and offices of Islamabad are selected and convenience sampling has been used to gather data of the age group between 18-32 years who are more conscious about brands and want to share the knowledge of their favorite brands. Results shows that the variables like customer service, trust in brand developed through its quality products, brand salience significantly impact on turning customers into advocates. However, commitment with a brand is not always necessary as customers more often seeks variety and desire to try newer and newer brands. Results show that Brand Love moderates the relationship among Differentiated Customer Service, brand salience, and Brand Advocacy but there is an insignificant moderating impact was found between brand commitment and brand advocacy. Our research was limited to the area of Islamabad Pakistan with a less and specific time frame and respondents. More extensive study could be done in future including other cities and industries. Keywords: Brand Advocacy, Brand Salience, Brand commitment, Brand Love, Differentiated Customer service, Consumer Behavior JEL Classifications: D3, L2